1995
DOI: 10.1128/jb.177.11.3259-3268.1995
|View full text |Cite
|
Sign up to set email alerts
|

Functional equivalence of Escherichia coli sigma E and Pseudomonas aeruginosa AlgU: E. coli rpoE restores mucoidy and reduces sensitivity to reactive oxygen intermediates in algU mutants of P. aeruginosa

Abstract: Mucoid colony morphology is the result of the overproduction of the exopolysaccharide alginate and is considered to be a major pathogenic determinant expressed by Pseudomonas aeruginosa during chronic respiratory infections in cystic fibrosis. Conversion to mucoidy can be caused by mutations in the second or third gene of the stress-responsive system algU mucA mucB. AlgU is 66% identical to the alternative sigma factor RpoE ( E ) from Escherichia coli and Salmonella typhimurium and directs transcription of sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
132
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(141 citation statements)
references
References 58 publications
8
132
1
Order By: Relevance
“…AlgU is 66 % identical to the ECF σ factor RpoE (Yu et al 1995) which is regulated via the regulated intramembrane proteolysis of the cognate anti-σ factor RseA in response to envelope stress signals in E. coli (Alba et al 2001(Alba et al , 2002Helmann 2002;Kanehara et al 2003;Walsh et al 2003). This mechanism of regulation is consistent in P. aeruginosa (Qiu et al 2007(Qiu et al , 2008Cezairliyan and Sauer 2009;Wood and Ohman 2009).…”
Section: Introductionsupporting
confidence: 53%
“…AlgU is 66 % identical to the ECF σ factor RpoE (Yu et al 1995) which is regulated via the regulated intramembrane proteolysis of the cognate anti-σ factor RseA in response to envelope stress signals in E. coli (Alba et al 2001(Alba et al , 2002Helmann 2002;Kanehara et al 2003;Walsh et al 2003). This mechanism of regulation is consistent in P. aeruginosa (Qiu et al 2007(Qiu et al , 2008Cezairliyan and Sauer 2009;Wood and Ohman 2009).…”
Section: Introductionsupporting
confidence: 53%
“…The initial experimental evidence supporting the hypothesis that algU encodes the P. aeruginosa equivalent of E was presented when E. coli rpoE was shown to complement an algU mutation and to induce mucoidy in P. aeruginosa (Yu et al, 1995). Biochemical evidence that algU encodes a sigma factor has been reported recently (Hershberger et al, 1995;Schurr et al, 1995b).…”
Section: Introductionmentioning
confidence: 97%
“…Because of this cascade of regulatory interactions, the net result of a loss of mucA is alginate overproduction and mucoid colony phenotype. The equivalence of E. coli E and P. aeruginosa AlgU suggests that there may be broader physiological overlaps in the function of these sigma factors (Yu et al, 1995). The sigma factor 32 that controls the heat-shock response in E. coli is encoded by the rpoH gene (Grossman et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Congruent with the functions played by the s E in E. coli, AlgT is involved in the regulation of a number of other systems in P. aeruginosa, such as heat shock, osmotic protection and protection against reactive oxygen species Yu et al, 1995;Firoved et al, 2002). It has also been shown that AlgT represses flagellum biosynthesis in P. aeruginosa (Tart et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Besides controlling alginate production, AlgT is the P. aeruginosa equivalent of the extreme heat-shock sigma factor s E of E. coli (Yu et al, 1995). Congruent with the functions played by the s E in E. coli, AlgT is involved in the regulation of a number of other systems in P. aeruginosa, such as heat shock, osmotic protection and protection against reactive oxygen species Yu et al, 1995;Firoved et al, 2002).…”
Section: Introductionmentioning
confidence: 99%